Unpacking Failures and Challenges in Flood Mitigation: An Actuating-Based Policy Implementation Analysis in West Aceh - Erlinda Sarni Sidim; Ikhwan Rahmatika Latif; Ilham Mirza Saputra; Aulia Risky; Karuni Humairah Arta; Najamudin Najamudin (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2026)
Flood disasters remain a recurrent and escalating risk in Indonesia, particularly in regions with high hydrometeorological vulnerability such as West Aceh Regency. This study aims to analyze the implementation of flood disaster mitigation policies at the local government level by employing George R. Terry’s actuating framework, which encompasses motivating, directing, communicating, and leading. A qualitative research approach was adopted, utilizing in-depth interviews, field observations, and document analysis to capture the dynamics of policy implementation in practice. The findings reveal that the effectiveness of flood mitigation in West Aceh is constrained by several interrelated factors, including low community participation, weak policy synchronization across institutions, limited communication systems, and insufficient leadership coordination. Although the local government has undertaken both structural measures—such as drainage improvement and flood control infrastructure—and non-structural measures—such as community awareness programs and institutional strengthening—these efforts remain fragmented and insufficiently integrated. As a result, mitigation outcomes have not yet significantly reduced the recurring flood risks. This study contributes to the literature by proposing an integrative conceptual framework that connects the actuating function with structural and non-structural mitigation approaches. The framework highlights that effective disaster mitigation is not solely dependent on technical interventions but also on the quality of policy execution, institutional capacity, and participatory governance. The study recommends strengthening institutional coordination, enhancing participatory communication strategies, and ensuring the integration of technical and social approaches in local disaster mitigation policies. These findings provide practical and theoretical implications for improving disaster governance in flood-prone regions, particularly within decentralized governance contexts.